Relaciones interpersonales y rendimiento académico de estudiantes de quinto y sexto grado primaria IEP Inmaculada Virgen de la Puerta Trujillo - Bocanegra Velasquez, Milagros Marilyn (2022)
This thesis was carried out with the purpose of analyzing the influence of interpersonal relationships on the academic performance of students in the fifth and sixth grade of the primary level of the IEP “Immaculate Virgin of the Door” - Trujillo District: 2018. The type of applied research has been considered, based on an explanatory design, and the sample consisted of 75 children, with whom we worked applying the methods and techniques of quantitative (survey) and qualitative (observation and interview) research. With the results obtained, it can be determined that these children have poor relationships between classmates and teachers, a situation that affects academic performance. This shows that the groups are increasingly heterogeneous and it is essential to promote positive attitudes in students to embrace such diversity as a source of enrichment and thus improve school performance. Finally, we propose to develop more educational practices that promote cooperative learning and the inclusion of these students in their work groups, and encourage them to participate, in addition to developing social skills, emotional intelligence, intercultural education, positive attitudes and developing in students the ability to establish good interpersonal relationships between peers. This thesis is subdivided into: I. Introduction: Problematic reality, background, theoretical basis and conceptual framework; II. Methodology; III. Results presentation; IV. Discussion of results. V. Conclusions ; VI. Recommendations, VII. Bibliographic references and Annexes.